2020
DOI: 10.1002/adfm.202000472
|View full text |Cite
|
Sign up to set email alerts
|

Localized Ostwald Ripening Guided Dissolution/Regrowth to Ancient Chinese Coin‐shaped VO2 Nanoplates with Enhanced Mass Transfer for Zinc Ion Storage

Abstract: Charge and mass transfer at the interface between electrode and electrolyte are of vital significance for energy conversion and storage in aqueous rechargeable zinc ion batteries (ZIBs). Approaching rational design and preparation of unique nanostructures with enhanced mass transfer is still facing great challenges in response to these problems. Herein, the highly uniform and round new‐state nsutite‐type vanadium dioxide (VO2) nanoplates with novel ancient Chinese coin structure (with thickness of ≈50 nm and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 50 publications
1
45
0
Order By: Relevance
“…The redox peaks observed in the CV curves of both electrodes are indistinguishable from the cathodic and anodic peaks described for many vanadium electrode materials. [ 24,51–54 ] The cycling performance of both cathodes at 0.2 C is displayed in Figure 3b,c, which shows that the PEDOT@YVO cathode system manifests extremely reversible (de)intercalation and a lower polarization reflecting the CVs results. YVO cathode achieves an initial discharge specific capacity of 125.5 mAh g −1 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The redox peaks observed in the CV curves of both electrodes are indistinguishable from the cathodic and anodic peaks described for many vanadium electrode materials. [ 24,51–54 ] The cycling performance of both cathodes at 0.2 C is displayed in Figure 3b,c, which shows that the PEDOT@YVO cathode system manifests extremely reversible (de)intercalation and a lower polarization reflecting the CVs results. YVO cathode achieves an initial discharge specific capacity of 125.5 mAh g −1 .…”
Section: Resultsmentioning
confidence: 97%
“…[ 35,70–72 ] Thus, Table S2 (Supporting Information) illustrates the comparison of long‐term cycling performance of this our composite electrodes (PEDOT@YVO) after 4000 cycles with other conducting polymer template and the state‐of‐the‐art V‐based cathodes in AZIBs. [ 54,66,73–77 ]…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 16c, benefiting from the ultrasmall nanostructure, such Mn 3 O 4 nanodots present a higher specific capacity and better rate capability compared with other Mn 3 O 4 samples reported previously. Unlike that, Cao et al [258] reported an Ancient Chinese Coin-shaped VO 2 nanoplates prepared based on the localized Ostwald ripening guided dissolution-regrowth method (Figure 16d,e). They also demonstrated that the mass transfer can be greatly enhanced on the surface of cathode, owing to the abundant ion accessibility and transfer pathways benefiting from the structural merits.…”
Section: D Materialsmentioning
confidence: 93%
“…Unlike that, Cao et al. [ 258 ] reported an Ancient Chinese Coin‐shaped VO 2 nanoplates prepared based on the localized Ostwald ripening guided dissolution‐regrowth method (Figure 16d,e). They also demonstrated that the mass transfer can be greatly enhanced on the surface of cathode, owing to the abundant ion accessibility and transfer pathways benefiting from the structural merits.…”
Section: Structural Engineering For Cathode Materialsmentioning
confidence: 96%
See 1 more Smart Citation